Total body water and acute kidney injury in myocardial infarction. (3rd May 2023) - Tapia, K; Barbosa, B; Croissant, Y; Costa, D; Acosta, M F; Gregorietti, V; Muzzio, M; Coronel, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Acute kidney injury (AKI) in patients with myocardial infarction (MI) is associated with higher morbidity and mortality and a higher incidence of MACE. The cardiorenal syndrome is a disorder between the heart and the kidney, where the primary dysfunction of one organ results in secondary dysfunction and damage to the other. There are multiple mechanisms involved in its pathogenesis, related to hemodynamic changes that lead to venous congestion, greater volume overload, and impaired renal function. Echocardiographic parameters of congestion have been related to AKI in MI. Our objective was to assess hydration estimated by bioimpedance analysis (BIA) as a marker of congestion and its association with AKI. Methods: Observational study in patients admitted to a CCU for MI and treated with PCI. Body composition was assessed with tetrapolar bioimpedance analysis obtained at 50 kHz. AKI was defined as a 1.5-fold increase in serum creatinine from baseline level within 24–48 hours. Mayor adverse cardiovascular events (MACE) during hospitalization were defined as type IV infarction, heart failure, stroke, or death. Results: A total of 94 patients were included. The median age was 58 years (IQR 53 – 63), and 89% were male. 53% had STEMI, 32% hypertension, 23% diabetes, and the median creatinine on admission was 0.9 mg/dl (IQR 0.75 – 1.05). AKI occurred in 9 patients (9.7%). Patients with AKI had a higher incidence of MACE (66.7% versus 29.8%, p = 0.02). Total body water (TBW) was higher on admission in patients who suffered AKI, compared to those who did not (76.8% versus 75.5%, p = 0.0008). There was no significant difference in TBW between patients who developed heart failure compared to those who did not (75.3% versus 75.8%, p = 0.39). Conclusion: Among patients with MI undergoing PCI, hydration status estimated by BIA, as a noninvasive parameter to estimate congestion, was associated with a higher risk of developing AKI. TBW according to AKI.